Pluralisme Dalam Novel Rumah di Seribu Ombak serta Implikasinya Terhadap Pembelajaran Sastra di SMA: Kajian Struktural Genetik - Aryo Febrian (UHAMKA Graduate School Thesis Abstract Collection, 2016)
This study aims to determine the elements of pluralism in the House in a Thousand Waves novel works of Erwin Arnada with structural genetic studies, and serve as an alternative learning materials Indonesian language and literature in high school This research is qualitative descriptive study with content analysis. The object of research is the Houses in a Thousand Waves novel work of Erwin Arnada. This study focuses on the element of pluralism that includes ethnic pluralism, political pluralism, pluralistic structure, the pluralist model, dual plural and media pluralism on the House in a Thousand Waves novel works of Erwin Arnada genetic and structural studies. The results showed that the House in a Thousand Waves novel work of Erwin Arnada, which analyzed had 60 sentences containing elements of pluralism, which is divided into ethnic pluralism 34 sentences, political pluralism second sentence, the structure of pluralistic 7 sentence, the pluralist model 9 sentence, dual pluralist 7 sentence and one sentence media pluralism. Based on the explanation proficiency level, ethnic pluralism which dominated the House in a Thousand Waves novel that tells about the harmonization of the immigrant population with the local population. Based on the analysis of 60 sentences pluralism and studied with genetic structuralism, there is an intrinsic element 102 is divided into the theme of 49 sentences, 21 sentences characterizations, plot 1 sentences, 17 sentences background, language style six sentences, and viewpoints 8 sentence. Then had 36 extrinsic elements are divided into social views author 6 sentences, 19 sentences work history, and 11 sentences of the author’s worldview.